Ankyloblepharon filiforme adnatum in trisomy 18 (Edwards's syndrome). Issue 6 (June 1985) - Clark, D I; Patterson, A
Abstract : Orbital and ocular abnormalities are commonly found in trisomy 18 (Edwards's syndrome). We believe this to be the first case reported in the literature of ankyloblepharon filiforme adnatum (AFA) occurring in Edwards's syndrome, and the literature on AFA is reviewed.